Frequency of Viral Hepatitis in Thalassemic Patients Receiving Multiple BIood Transfusions - Falah Salim Manhal (Iraqi National Journal of Nursing Specialties, 2023)
Objective: The present study was conducted during the period from october lst 2007 to May lst 2008. The aim of this study was to estimate the prevalence of viral hepatitis in a group of Iraqi thalassemic patients receiving multiple transfusions compared with pre-transfused thalassemic patients and apparently healthy controls. Methodology: BIood samples were collected from one hundred patients, 50 samples from patients with beta thalassemia major referred to Al-Abbas Hosphal in Al-Kut City and 50 samples from apparently healthy blood donors in blood banl(, jn addition to 25 blood samples from pre-transfused thalassemic patients. Hepatitis 8 surface antigen (HBSAg), anti-hepatitis A virus (HAV), and anti-hepatitis C virus (HCV) antibodies were checked by using a second-generation enzyme-linked immunosorbent assay (ELISA). Results: Hepatitis 8 surface antigen, anti-HAV, and anti-HCV antibodies were positive in four of 50 (8%, 95% confidence interval (CI)=0.17-I.3), two of 50 (2%; 95% CI=12.6-19.2), and 16 of 50 (32%; 95% confidence interval (CI)=0.12-2.3), respectively. Positive sera for anti-HAV Abs were found in 2 of 25 (8%) pre-transfused patients. Positive sera for anti-HCV Abs were found in 2 of 50 (4°/o) healthy control. The rate of anti-HCV Ab was significantly higher in multitransfused patients than in the pretransfused and control groups (P < 0.01). Conclusions: It was concluded that HCV is the current major problem in multitransfused patients with thalassemia major. Recommendations: More careful pretransfusion screening of blood for anti-HCV must be introduced in our blood banks. More cohort studies are needed by applying advanced molecular techniques for accurate viral detection.